PENGARUH PEMBERIAN AIR TERHADAP PERTUMBUHAN DAN HASIL SORGUM (Sorghum bicolur L. Moench) LOKAL RARA TADDA - Rambu Hara, Enjelita; Danga Lewu, Lusia (Jurnal Biogenerasi, 2024)
Sorghum is a cereal food crop that is still in the same family as corn, rice and wheat. The basic problem in the development of sorghum is the maturity of the soil or its availability in the soil. This study aims to determine the effect of water provision that can increase the growth and yield of sorghum using RAL (completely randomized design) consisting of 5 treatments 4 replications The methods used include plant height, number of leaves, panicle length, wet stalk weight, seed weight per 1000 grains, and dry stalk weight. With various levels of water provision that vary P0 = (control) P1 = once every 2 days P2 = once every 4 days P3 = once every 6 days P4 = once every 8 days. Based on the results of the research that has been conducted, it can be concluded that the growth of sorghum plants with the highest value is found in treatments p3 and p4 both in plant height, number of leaves, panicle length, 1000 grain seed weight, wet bunch weight and dry bunch weight. The higher the growth and yield of sorghum plants, the higher the production value of sorghum plants will be, while the lowest values ​​of P1 and P2 are not much different from treatments P3 and P4 and the effect of watering sorghum plants has a significant effect on all parameters.